Zhodnocení MRI nálezů na šlachovém štěpu po anatomické rekonstrukci předního zkříženého vazu u pacientů s aplikací versus bez aplikace fibrinu bohatého na krevní destičky – výsledky prospektivní randomizované studie - Zeman, P; Kasl, J; Tupý, R; Frei, R; Kott, O; Kautzner, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
PURPOSE OF THE STUDY The purpose of the prospective randomised study was to assess the benefits of the platelet-rich fibrin (PRF) application during the anatomic anterior cruciate ligament reconstruction (ACLR) for tendon graft healing. MATERIAL AND METHODS The study included 40 patients with an isolated rupture of the anterior cruciate ligament in the knee. The MRI findings on the tendon graft were evaluated at 6 months and 12 months after the surgery in a total of 33 patients, namely in 10 women/23 men (21 right knee/12 left knee), with the mean age of 29.1 years and at the mean follow-up of 15.9 weeks after the injury. The randomisation using envelopes was carried out at the beginning of arthroscopy either in the group with the PRF application (Group 1) (17 patients) or in the group without the PRF application (Group 2) (16 patients). The followed-up patients underwent the ACLR with targeting the femoral tunnel through anteromedial portal using the autografts of m. semitendinosusand m. graciliswith Tightrope femoral fixation and Inion implant in tibia. In Group 1, during the surgery PRF was applied both in the drilled tunnels (intraosseously) and directly to the surface of the tendon graft itself (intraarticular part). The Group 2 was a control group in which the same intervention was performed, however without the PRF application. In the 6 th and 12 th month after the surgery, the signal intensity of the knee and occurrence of the ACL graft failure, bone (marrow) oedema rate near the tunnels were assessed by an independent radiologist using a 3 Tesla MRI. RESULTS In the 6 th and also in the 12 th postoperative month, neither a complete, nor a partial graft failure was found in the group with PRF, whereas in Group 2 a complete or a partial graft failure was observed in 12.5% (p = 0.23). In the 6th month, a bone marrow oedema near the intraosseous parts of the graft was reported in 94.1% of patients in Group 1 and in 81.3% of patients in Group 2, while in the 12 th month it was 23.5% of evaluated patients in Group 1 and 37.5% patients in Group 2. The differences between the two groups were not statistically significant in the 6 th (p = 0.096) or in the 12 th month (p = 0.43). In the 6 th month, a fully ligamentised graft was found in 52.9% of patients in Group 1 and in 37.5% of patients in Group 2 (p = 0.061), a partially ligamentised graft was present in 47.1% of patients in Group 1 and in 50% of patients in Group 2. In the 12 th month, a fully ligamentised graft was seen in 94.1% of patients in Group 1 and in 75% of patients in Group 2 (p = 0.26) and a partially ligamentised graft was present in 5.9% of patients in Group 1 and in 12.5% of patients in Group 2. In the remaining 12.5% of patients in Group 2, the finding was assessed as a graft with no signs of ligamentisation. DISCUSSION We have not encountered a paper in the Czech or world literature which would present results of a similar study, i.e. which would evaluate the potential benefits of the platelet-rich fibrin application in the course of the anatomic anterior cruciate ligament reconstruction. Majority of studies evaluate the benefits of the application of platelet-rich plasma aimed to achieve a positive effect on the LCA graft healing. CONCLUSIONS Our study proved a higher percentage of ligamentisation and healed grafts into the bone as well as a lower occurrence of graft failure in the group with PRF compared to the group without the PRF application, namely both in the 6 th and in the 12 th month. Nonetheless, the differences between the two groups assessed at the same time were not statistically significant. Key words: anterior cruciate ligament, arthroscopy, anatomic ACL reconstruction, magnetic resonance imaging of the graft, platelet-rich fibrin, graft healing, MRI signal intensity of the graft.
Keywords: rejekce štěpu; Femur; Platelet-Rich Plasma; Tendons; Male; Tibia; Rupture; Knee Joint; Česká republika; tibie; Arthroscopy; artroskopie; plazma bohatá na destičky; mužské pohlaví; Platelet-Rich Fibrin; šlachy; Prospective Studies; Adult; Czech Republic; poranění předního zkříženého vazu; magnetická rezonanční tomografie; fibrin bohatý na krevní destičky; Magnetic Resonance Imaging; Transplantation, Autologous; ženské pohlaví; ruptura; Graft Rejection; Humans; kolenní kloub; prospektivní studie; Anterior Cruciate Ligament; Anterior Cruciate Ligament Reconstruction; rekonstrukce předního zkříženého vazu; autologní transplantace; femur; dospělí; Anterior Cruciate Ligament Injuries; Female; lidé; ligamentum cruciatum anterius